Importance of aerosol composition and aerosol vertical profiles in global spatial variation in the relationship between PM2.5 and aerosol optical depth - H. Zhu; R. V. Martin; A. van Donkelaar; M. S. Hammer; C. Li; J. Meng; C. R. Oxford; X. Liu; Y. Li; D. Zhang; I. Singh; A. Lyapustin (Atmospheric Chemistry and Physics, 2024)
Ambient fine particulate matter (PM2.5) is the leading global environmental determinant of mortality. However, large gaps exist in ground-based PM2.5 monitoring. Satellite remote sensing of aerosol optical depth (AOD) offers information to help fill these gaps worldwide when augmented with a modeled PM2.5–AOD relationship. This study aims to understand the spatial pattern and driving factors of this relationship by examining η (<mstyle displaystyle="false">PM2.5AOD</mstyle><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="23pt" height="18pt" class="svg-formula" dspmath="mathimg" md5hash="eee837ecf92d4ea3f198e8284fd7e842"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-24-11565-2024-ie00001.svg" width="23pt" height="18pt" src="acp-24-11565-2024-ie00001.png"/></svg:svg>) using both observations and modeling. A global observational estimate of η for the year 2019 is inferred from 6870 ground-based PM2.5 measurement sites and satellite-retrieved AOD. The global chemical transport model GEOS-Chem, in its high-performance configuration (GCHP), is used to interpret the observed spatial pattern of annual mean η. Measurements and the GCHP simulation consistently identify a global population-weighted mean η value of 96–98 µg m−3, with regional values ranging from 59.8 µg m−3 in North America to more than 190 µg m−3 in Africa. The highest η value is found in arid regions, where aerosols are less hygroscopic due to mineral dust, followed by regions strongly influenced by surface aerosol sources. Relatively low η values are found over regions distant from strong aerosol sources. The spatial correlation of observed η values with meteorological fields, aerosol vertical profiles, and aerosol chemical composition reveals that spatial variation in η is strongly influenced by aerosol composition and aerosol vertical profiles. Sensitivity tests with globally uniform parameters quantify the effects of aerosol composition and aerosol vertical profiles on spatial variability in η, exhibiting a population-weighted mean difference in aerosol composition of 12.3 µg m−3, which reflects the determinant effects of composition on aerosol hygroscopicity and aerosol optical properties, and a population-weighted mean difference in the aerosol vertical profile of 8.4 µg m−3, which reflects spatial variation in the column–surface relationship.